Lin‐Gettig syndrome: Craniosynostosis expands the spectrum of the KAT6B related disorders. Issue 10 (11th July 2017) - Bashir, Rani A.; Dixit, Abhijit; Goedhart, Caitlin; Parboosingh, Jillian S.; Innes, Allan M.; Ferreira, Patrick; Hasan, Shabih U.; Au, Ping‐Yee B.
Abstract : We report two patients with sagittal craniosynostosis, hypoplastic male genitalia, agenesis of the corpus callosum, thyroid abnormalities, and dysmorphic features which include short palpebral fissures and retrognathia. The clinical presentation of both patients was initially thought to be suggestive of Lin‐Gettig syndrome (LGS), a multiple malformation syndrome associated with craniosynostosis that was initially reported in two brothers in 1990, with a third patient reported in 2003. Our first patient was subsequently found through exome sequencing to have a de novo mutation in KAT6B, c.4572dupT, p.(Thr1525Tyrfs*16). The second patient was ascertained as possible LGS, but KAT6B mutation testing was pursued clinically after the identification of the KAT6B mutation in Patient 1, and identified a de novo mutation, c.4205_4206delCT, p.(Ser1402Cysfs*5). The phenotypic spectrum of KAT6B mutations has been expanding since identification of KAT6B mutations in genitopatellar syndrome (GPS) and Say Barber Biesecker Young Simpson (SBBYS) syndrome patients. We show that craniosynostosis, which has not been previously reported in association with KAT6B mutations, may be part of the genitopatellar/Say Barber Biesecker Young Simpson spectrum. These two patients also further demonstrate the overlapping phenotypes of genitopatellar and SBBYS syndromes recently observed by others. Furthermore, we propose that it is possible that one or more of the previous cases of LGS may have also been due to mutation in KAT6B, and that LGS may actually be a variant within the KAT6B spectrum and not a distinct clinical entity.